3(x-7)+4=12

Simple and best practice solution for 3(x-7)+4=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-7)+4=12 equation:


Simplifying
3(x + -7) + 4 = 12

Reorder the terms:
3(-7 + x) + 4 = 12
(-7 * 3 + x * 3) + 4 = 12
(-21 + 3x) + 4 = 12

Reorder the terms:
-21 + 4 + 3x = 12

Combine like terms: -21 + 4 = -17
-17 + 3x = 12

Solving
-17 + 3x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 3x = 12 + 17

Combine like terms: -17 + 17 = 0
0 + 3x = 12 + 17
3x = 12 + 17

Combine like terms: 12 + 17 = 29
3x = 29

Divide each side by '3'.
x = 9.666666667

Simplifying
x = 9.666666667

See similar equations:

| 4k-3=k+4 | | -6+6r=-(-7r+2) | | X+2/5=7/10 | | (-1/14)(x) | | -8(8b-2)=-176 | | 6x+4=2(x+1) | | 1/2(x-6)=17 | | 286=4x-6(6x-5) | | 57.99*0.11x=58.54 | | 3x+5-8x-7=-27 | | 2-5(3+5r)=-113 | | ((7t^2)+8)/t | | -3+2x+10+x=7 | | 7y-20y-31=14y+8 | | 8(-2n+8)=160 | | 3x^2+5x+5=0 | | 3x+7.35=14.26 | | 6+2(-3)=-3+5+-3 | | 2g+a/x=4w | | 6(4x-9)-4=6(x-4)+56 | | 9x-3+4x-4=-59 | | k/14=0 | | x+6=8+7x | | 3u^2-12u+13=0 | | 0.5x+8/7x=x+36 | | 12x-1+1+2x=14 | | 3x-15+5x+59=180 | | -15=-3x+6 | | -2x+5(8x-6)=9-x | | -12=8+(f/2) | | 24x+4+2=3(10x-1) | | 2/3p+1/2=p-3 |

Equations solver categories